2010
DOI: 10.1007/s10142-009-0152-9
|View full text |Cite
|
Sign up to set email alerts
|

Light and temperature regulated terpene biosynthesis: hepatoprotective monoterpene picroside accumulation in Picrorhiza kurrooa

Abstract: Picrorhiza (Picrorhiza kurrooa) is an endangered medicinal plant with well-known hepatoprotective activity attributed to monoterpenoid picrosides. The present article details on regulatory genes of terpenoid metabolism, 3-hydroxy-3-methylglutaryl coenzyme A reductase (pkhmgr) and 1-deoxy-D-xylulose-5-phosphate synthase (pkdxs) from picrorhiza. Since no molecular information was available, these genes were cloned to full-length by degenerate primers and rapid amplification of cDNA ends, followed by cloning of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 53 publications
2
42
0
Order By: Relevance
“…Three organs (root, shoot, and stolon) together with their in vitro culture counterparts were chosen for investigation of miRNA expression specific to each condition. Due to wellknown pharmacological relevance of picrosides, several attempts have been made to understand the biosynthesis and accumulation of picrosides in P. kurroa in the past (Kawoosa et al 2010;Sood and Chauhan 2010), however, still the molecular basis of biomass yield and picrosides content is not thoroughly understood in P. kurroa. Therefore, current study was aimed at identification of miRNAs which possibly regulate the biological and physiological processes contributing to biomass yield and metabolites content in different organs of P. kurroa.…”
Section: Introductionmentioning
confidence: 99%
“…Three organs (root, shoot, and stolon) together with their in vitro culture counterparts were chosen for investigation of miRNA expression specific to each condition. Due to wellknown pharmacological relevance of picrosides, several attempts have been made to understand the biosynthesis and accumulation of picrosides in P. kurroa in the past (Kawoosa et al 2010;Sood and Chauhan 2010), however, still the molecular basis of biomass yield and picrosides content is not thoroughly understood in P. kurroa. Therefore, current study was aimed at identification of miRNAs which possibly regulate the biological and physiological processes contributing to biomass yield and metabolites content in different organs of P. kurroa.…”
Section: Introductionmentioning
confidence: 99%
“…Light is a major environmental signal for the differential accumulation of isoprenoid-derived metabolites during plant growth and development. For example, illumination in Picrorhiza kurroa promotes the synthesis of monoterpene picroside (Kawoosa et al, 2010). This result is concomitant with the light-dependent accumulation of the transcripts of HMGS and DXS, which are key genes in the MVA and MEP pathways, respectively (Kawoosa et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…], fruit temperature may reach levels that are detrimental to terpene biosynthesis. Kawoosa et al (2010) reported that genes involved in terpene synthesis can be down-regulated at temperatures above 25 ºC. In this study, daily air temperatures at the fruit zone during veraison (mid-January) were 50% of the time above 30 ºC, which may explain the low concentrations of volatile compounds reported here.…”
Section: Concentration Of Volatile Compoundsmentioning
confidence: 59%